2019
DOI: 10.1044/2019_jslhr-s-18-0493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Encouraging the Use of Gestures on Speech

Abstract: Purpose Previous studies have investigated the effects of the inability to produce hand gestures on speakers' prosodic features of speech; however, the potential effects of encouraging speakers to gesture have received less attention, especially in naturalistic settings. This study aims at investigating the effects of encouraging the production of hand gestures on the following speech correlates: speech discourse length (number of words and discourse length in seconds), disfluencies (filled pauses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
(68 reference statements)
3
21
0
1
Order By: Relevance
“…However, recent work suggests that gesturespeech physics does generalize to fluent speech. For example, Cravotta and colleagues 47 found that encouraging participants to gesture during cartoon narration versus giving no instructions led to a 22-Hz increase in observation of max F0 and to greater F0 ranges of speech and intensity. Furthermore, computational modelers have reported interesting successes in synthesizing gesture kinematics on the basis of speech acoustics alone, 48,49 indicating that information about body movements inhabits the speech signal (see also Refs.…”
Section: Gesture-speech Physicsmentioning
confidence: 99%
“…However, recent work suggests that gesturespeech physics does generalize to fluent speech. For example, Cravotta and colleagues 47 found that encouraging participants to gesture during cartoon narration versus giving no instructions led to a 22-Hz increase in observation of max F0 and to greater F0 ranges of speech and intensity. Furthermore, computational modelers have reported interesting successes in synthesizing gesture kinematics on the basis of speech acoustics alone, 48,49 indicating that information about body movements inhabits the speech signal (see also Refs.…”
Section: Gesture-speech Physicsmentioning
confidence: 99%
“…However, recent work suggests that gesture-speech physics does generalize to fluent speech. For example, Cravotta and colleagues 47 found that encouraging participants to gesture during cartoon narration versus giving no instructions lead to 22Hz increase in observation of max F0 and to greater F0 ranges of speech and intensity. Furthermore, computational modelers have reported on interesting successes in synthesizing gesture kinematics based on speech acoustics alone 48,49 , indicating that information about body movements inhabits the speech signal (see also 50,51 ).…”
Section: Gesture-speech Physicsmentioning
confidence: 99%
“…A subset of 8 comic strip illustrations was chosen from the Simon's Cat comic series that were used in Cravotta et al (2019). These 8 comic strips were chosen based on the ease of translating the illustrations to a short narrative that could be understood by low-intermediate level language learners.…”
Section: Materials Stimuli Creation For the Drawing Taskmentioning
confidence: 99%